FISH DIVERSITY OF SARNI RESERVOIR WITH SPECIAL REFERENCE TO THREATS AND CONSERVATION MEASURES - RAY, A. BHOWMIK; SHARMA, A. P.; PATRA, B. C.; CHOUDHURY, S. ROY (Journal of the Inland Fisheries Society of India, 2020)
Documented and updated the fish diversity of Sarni, a medium sized reservoir in Betul district of Madhya Pradesh. The study revealed occurrence of 39 fish species classified under 25 genera and 10 families; Catla catla  was the most abundant species among Indian major carps. Sarni reservoir supported reasonably good fish diversity, but adequate conservation measures are required  in  face of the  increased man-induced activities. Issues related to various threats to aquatic environment and conservation strategies in the reservoir have been discussed.Key words: Reservoir, piscine fauna, Sarni reservoir, diversity.